Pro PHP and jQuery - Lengstorf, Jason; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2010)
This book is for intermediate programmers interested in building Ajax web applications using jQuery and PHP. Along with teaching some advanced PHP techniques, it will show you how to take your dynamic applications to the next level by adding a JavaScript layer with jQuery. Learn to utilize built-in PHP functions to build calendar tools. Learn how jQuery can be used for Ajax, animation, client-side validation, and more.
Keywords: Computer programming; Software engineering; Web Development; Software Engineering/Programming and Operating Systems